Drug Pricing of Domestic Anti-PD-L1 Antibody Adebrelimab: Cost-Effectiveness Analysis of the First-Line ES-SCLC Treatment in China - Zhou D; Dong X; Zhou Z; Liu Q (Dove Medical Press, 2023)
Dongchu Zhou,1 Xinrui Dong,1 Zhen Zhou,2 Qiao Liu1 1Department of Pharmacy, The Second Xiangya Hospital of Central South University, Changsha, People's Republic of China; 2School of Public Health and Preventive Medicine, Monash University, Melbourne, VIC, AustraliaCorrespondence: Qiao Liu, Department of Pharmacy, The Second Xiangya Hospital, Central South University, Changsha, Hunan, 410000, People's Republic of China, Email liuqiao6767@csu.edu.cnPurpose: The market price of adebrelimab, the first Chinese-developed anti-PD-L1 antibody used as a first-line treatment for extensive stage-small-cell lung cancer (ES-SCLC), has garnered significant public attention. This study sought to investigate the affordable price of adebrelimab for Chinese patients with untreated ES-SCLC through a cost-effectiveness analysis.Patients and Methods: We conducted a cost-effectiveness analysis using a Markov model, incorporating a what-if scenario of adding adebrelimab to first-line etoposide/platinum (EP) chemotherapy is cost-effective for ES-SCLC patients from the perspective of the Chinese healthcare system. The model included three mutually exclusive health states, with transition probabilities derived from the CAPSTONE-1 trial. Health state utilities and costs were acquired from a myriad of authoritative sources. We compared the incremental cost-effectiveness ratios (ICERs) for adebrelimab plus EP chemotherapy (AEP) versus EP with a willingness-to-pay threshold of $37,654 per quality-adjusted life-years (QALYs) to estimate the affordable price ceiling of the upcoming adebrelimab.Results: For the entire ES-SCLC population, the estimated price ceiling of adebrelimab/mg was $0.542 (95% CI, $0.542-$0.552). Subgroup analyses found that the highest price ceiling of adebrelimab/mg was observed in ES-SCLC patients with lactate dehydrogenase concentration ≤ upper normal limit [$0.824 (95% CI, $0.815-$0.830)]; and the lowest was found in ES-SCLC patients with liver metastasis [$0.252 (95% CI, $0.250- $0.256)]. Sensitivity analysis revealed a heightened probability of cost-effectiveness for the first-line AEP as the price of adebrelimab decreased, encompassing both the entire ES-SCLC population and its subgroups.Conclusion: The affordable price range for adebrelimab/mg Chinese patients with untreated ES-SCLC was estimated to be between $0.252 and $0.824, with variations observed across different subgroups. In the context of universal healthcare coverage, our study provides valuable evidence to inform the implementation of a value-based pricing strategy for cancer treatment.Keywords: cost-effectiveness, extensive stage-small-cell lung cancer (ES-SCLC), adebrelimab, drug pricing, China